Enuma Elis. The Babylonian Epic of Creation. The cuneiform text. Text established by W. G. Lambert and copied out by Simon B. Parker. Oxford, Clarendon Press; reimpresión 1967. 47 pp. - Silva Castillo, Jorge (Estudios de Asia y África, 1969)
-